Mid-century modern : interiors, furniture, design details - Quinn, Bradley (Conran Octopus, 2004)
Explores the interior decor of the nineteen fifties house, examining walls, flooring, surfaces, lighting, and furniture, and includes case studies of present-day homes exhibiting mid-century style